2005
DOI: 10.1037/1091-7527.23.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Family Rules About Exposure to Environmental Tobacco Smoke.

Abstract: Environmental tobacco smoke (ETS) is detrimental to the health of children. It is important for families to implement rules that limit the exposure of children both within the home and in the community. The current study used a diverse sample of participants from pediatric clinics in a large metropolitan area to explore what restrictions families place on tobacco use in their home and in the community (e.g., restaurants, trains). In general, minority ethnic groups were less likely than their Caucasian peers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…Exposure to SHS can be reduced by over 80% through the elimination of smoking in public spaces and Yet, in both pediatric and family practice offices, fewer than half of parents are asked about exposure to SHS in the home, and only one third of smoking parents are counseled about the risks of SHS exposure for children (Winickoff et al, 2003). Recent research has revealed that parents vary considerably on the rules for smoking in the household (Pyle, Haddock, Hymowitz, Schwab, & Meshberg, 2005) and typically do not intervene to avoid SHS exposure for their children in cars or on trains, where the toxins are as much as 23 times more concentrated. Even less is known about screening and counseling for SHS exposure for adults.…”
Section: Exposure To Shsmentioning
confidence: 99%
“…Exposure to SHS can be reduced by over 80% through the elimination of smoking in public spaces and Yet, in both pediatric and family practice offices, fewer than half of parents are asked about exposure to SHS in the home, and only one third of smoking parents are counseled about the risks of SHS exposure for children (Winickoff et al, 2003). Recent research has revealed that parents vary considerably on the rules for smoking in the household (Pyle, Haddock, Hymowitz, Schwab, & Meshberg, 2005) and typically do not intervene to avoid SHS exposure for their children in cars or on trains, where the toxins are as much as 23 times more concentrated. Even less is known about screening and counseling for SHS exposure for adults.…”
Section: Exposure To Shsmentioning
confidence: 99%
“…Overall, approximately 60% of those surveyed by Pyle et al (2005) do not allow smoking in their house, 20% allow adults to smoke in certain rooms at certain times, and 55% request that adults smoke outside the house. There were important subgroup differences depending on ethnicity and whether there was a smoker in the house.…”
Section: Who Makes the Rules?mentioning
confidence: 99%
“…The focus of Pyle et al's (2005) report is on family rules that are established among adult family members as well as adults outside the household. Frequently, one thinks of rules being established between children and adults, with adults setting the rules.…”
Section: Who Makes the Rules?mentioning
confidence: 99%
See 1 more Smart Citation
“…10,16,[23][24][25] However, smoke-free policies are more prevalent among households with younger residents 10 and those that include a nonsmoking adult. 10,[24][25][26][27][28] Smokers whose families preferred they did not smoke were also more likely to have smoking restrictions at home. 10,29 In fact, previous research suggests that the factors most likely to influence the probability of restricted smoking among households with smoking residents include concern for the health of a nonsmoker and interest by another family member in the smoker's quitting, 10 rather than the smoker's desire to have a more successful quit attempt.…”
mentioning
confidence: 99%